Multi-instrument comparisons of D-region plasma measurements - Friedrich, M.; Torkar, K. M.; Hoppe, U.-P.; Bekkeng, T.-A.; Barjatya, A.; Rapp, M. (Annales Geophysicae, 2013)
The ECOMA (Existence and Charge state Of Meteoric dust grains in the middle Atmosphere) series of sounding rocket flights consisted of nine flights with almost identical payload design and flight characteristics. All flights carried a radio wave propagation experiment together with a variety of plasma probes. Three of these measured electron densities, two ion densities. The rockets were all launched from the Andøya Rocket Range, Norway, in four campaigns between 2006 and 2010. Emphasis is on the final three flights from 2010 where the payloads were equipped with four instruments capable of measuring plasma densities in situ, among them a novel probe flown for the first time in conjunction with a wave propagation experiment. Deviation factors of all probe data relative to the wave propagation results were derived and revealed that none of the probe data were close to the wave propagation results at all heights, but – more importantly – the instruments showed very different behaviour at different altitudes. The novel multi-needle Langmuir probe exhibits the best correlation to the wave propagation data, as there is minimal influence of the payload potential, but it is still subject to aerodynamics, especially at its location at the rear of the payload. For all other probe types, the deviation factor comes closer to unity with increasing plasma density. No systematic difference of the empirical deviation factor between day and night can be found. The large negative payload potential in the last three flights may be the cause for discrepancies between electron and ion probe data below 85 km.